In Vitro Evaluation of Flexural Strength of Different Skin Staples - Theofilaktidou, Μaria; Pavlidis, Leonidas; Savvas, Ioannis; Angellou, Vasileia; Argyros, Apostolos; Michailidis, Nikolaos; Papazoglou, Lysimachos G. (VCOT Open, 2024)
Objective The aim of the study was to assess the flexural deformation strength of various brands of skin staples postfiring, and to compare the distance and alignment of the staple tips.Study Design In this experimental in vitro study, nine types of commercially available skin staples were tested. Following firing, six staples of each type were mounted on a material testing machine. Mechanical properties of staples were evaluated under uniaxial loading test, which translated to the bending of the staple for determination of flexural deformation strength. Staples were evaluated for tip alignment and distance between pointed tips.Results Maximum force to flexural deformation was greater for Precise (29.633 ± 7.8421 N), than Proximate (16.200 ± 1.1541 N; p = 0.000), Henry Schein (23.383 ± 5.2282 N; p = 0.011), Weck Visistat (24.329 ± 1.0372 N; p = 0.025), Appose (18.133 ± 1.2675 N; p = 0.000), Manipler (14.067 ± 3.7393 N; p = 0.000), and Leukoclip (22.288 ± 1.6915 N; p = 0.002) but was not different from Gima (27.483 ± 6.5637 N; p = 0.370) and Advan (27.283 ± 2.8708 N; p = 0.327) Precise, Appose, and Advan fired staples had their pointed tips met, whereas Manipler, Leukoclip, Gima, Henry Schein, Proximate, and Weck Visistat showed a gap between pointed tips. Proximate staples also showed malalignment between their pointed tips.Conclusion The flexural deformation strength of skin staples manufactured by Precise, Gima, and Advan was between 29 and 27 N and thus significantly superior to the other six staple types tested.
Keywords: bioengineering; biomechanics; soft-tissue surgery; skin and soft-tissue reconstruction; wound management